Studi Kajian Ketidaksetaraan Gender dalam Iklan Televisi Promo Detergen Attack Easy - Dinda Gita Puspita; Solihah Titin Sumanti (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
This study aims to investigate the representation of women in television advertisements for Attack Easy detergent promotions and analyze gender inequality based on subordination, workload, and gender and sex differences. The study employed qualitative research and Roland Barthes's semiotic analysis to explore the relationship between signifiers and signs in a sign with denotations and connotations. The findings revealed a complex portrayal of gender, including both gender equality and gender imbalance. While women are depicted as capable of performing heavy work typically done by men, they are still relegated to the role of housewives and remain subordinate in society. Additionally, gender differences are often conflated with sex differences, contributing to ongoing misunderstandings about the nature of gender inequality. Overall, this research underscores the need for more nuanced representations of gender in media and highlights the ongoing challenges facing efforts to achieve gender equality in society.